Bidirectional single-loop current sensorless control applied to NPC multi-level converter considering conduction losses - Alexander Suzdalenko; Janis Zakis; Pavels Suskis; Leonids Ribickis (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
The current feedback is considered as unavoidable part of most control system driving power electronic converters. However, it is possible to eliminate the use of current sensor, if properly calculated volt-second balance is applied to input inductor. This paper describes the implementation of current sensorless control technique applied to neutral point clamped multi-level converter, where only voltage control-loop is used to stabilize internal capacitors voltage, while inductor’s current is shaped by means of current sensorless control block in both discontinuous and continuous current modes. The capacitor voltage balancing is implemented by means of delta-controller that selects alternative capacitor in respect to main switching scheme. Finally, the analytical study of proposed solution is verified with simulation results.